2020
DOI: 10.1097/meg.0000000000001954
|View full text |Cite
|
Sign up to set email alerts
|

Role of ursodeoxycholic acid on maternal serum bile acids and perinatal outcomes in intrahepatic cholestasis of pregnancy

Abstract: Aim Intrahepatic cholestasis of pregnancy (ICP) is associated with safe maternal outcomes but perinatal outcomes have been variable. We assessed clinical factors and impact of bile acid levels on maternal and neonatal outcomes in ICP. Methods Patients with ICP (defined as pruritus with serum bile acids ≥ 10 mmol/l) were included prospectively with an assessment of risk factors, modes of delivery as well as maternal and neonatal outcomes. Mild and severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 40 publications
0
14
0
Order By: Relevance
“…Clinical treatment of ICP is aimed at improving patient symptoms and fetal prognosis [ 9 ]. Thus, UDCA is the first-line drug for the treatment of ICP and is essential in improving the pregnancy outcomes of patients with ICP [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Clinical treatment of ICP is aimed at improving patient symptoms and fetal prognosis [ 9 ]. Thus, UDCA is the first-line drug for the treatment of ICP and is essential in improving the pregnancy outcomes of patients with ICP [ 9 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical treatment of ICP is aimed at improving patient symptoms and fetal prognosis [ 9 ]. Thus, UDCA is the first-line drug for the treatment of ICP and is essential in improving the pregnancy outcomes of patients with ICP [ 9 , 10 ]. The drug is characterized by safety, effectiveness, high compliance, and convenience and is widely used in clinical practice [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies conducted on pregnant women with intrahepatic cholestasis of pregnancy among the world population have investigated the morbidity. The incidence of intrahepatic cholestasis of pregnancy varies greatly among ethnic groups and geographic regions, ranges from 0.2% to 2.0%, which occurs most frequently in South American and Northern European ethnic groups [17,32]. In the study period, a total of 27,058 deliveries at our hospital, of these, 751 women (2.8%) were diagnosed with intrahepatic cholestasis of pregnancy.…”
Section: Discussionmentioning
confidence: 93%
“…Intrahepatic cholestasis of pregnancy has been consistently associated with a higher incidence of adverse pregnancy outcomes, including spontaneous and iatrogenic preterm delivery, non-reassuring fetal status, meconium staining of the amniotic fluid, and still birth [13][14][15]. The risk of complications for the fetus is associated with the serum level of maternal serum bile acids, and women with more severe cholestasis are at greater risk [2,16,17]. Previous studies mainly focused on the effects of intrahepatic cholestasis of pregnancy on pregnant mothers and fetuses, and few studies reported the postpartum growth and development of fetuses in pregnant women with intrahepatic cholestasis of pregnancy.…”
Section: Introductionmentioning
confidence: 99%